Pasture management - Bickford, Rick. (Chatswood, NSW ; Stoneham [Mass.], USA : Inkata Press, 1995)
This text covers all aspects of pasture management. It focuses on pasture grasses and legumes, weeds and pest species, tillage and sowing techniques, soil testing and fertilizer requirements, fodder species, mowing times, conservation techniques and machinery and storage measures
Includes index.
rpm 26/08/16
Loans
Keywords: Pastures -- Australia-- Management; Pastures-- Management; Australia